President's Annual Report, 1989-1990 - Bailey, Hugh C. (Valdosta State University Archives and Special Collections, 1990)
The Valdosta State College Annual Report of the President for fiscal year 1989-1990 by Hugh C. Bailey.
Keywords: Valdosta State University; College publications; Corporate reports; College presidents